REVIEW ALGORITMA C-THETA* DAN PROSPEK IMPLEMENTASINYA DI MASA DEPAN - Nathanael Aldo Phillip (JURNAL TEKNIK INFORMATIKA, 2017)
RETRACTION TO: Phillip, N. A. (2017). Review Algoritma C-Theta* dan Prospek Implementasinya Di Masa Depan. Jurnal Teknik Informatika, 10(2), 129-136. doi: 10.15408/jti.v10i2.6991We wish to retract this article due to request received from author to retract the article from Jurnal Teknik Informatika Volume 10 (2) 2017.We deeply regret any inconvenience this publication has caused for others.